Metode Pendidikan Akhlak di Pondok Pesantren Imam Bukhari Surakarta - Haerullah, Haerullah; Anshory, Muhammad Isa (TSAQOFAH, 2024)
Forming noble morals requires a planned and consistent method. The importance of methods in moral education is urgent. Pesantren are often places where Islamic religious education is taught in depth. This includes moral teachings, ethics, and good principles in daily life in accordance with religious teachings. This article aims to find out the educational methods applied at Imam Bukhari Islamic Boarding School. The research was conducted by qualitative methods. Data collection was done by interviews and observations.